On Centromeres’ Evidential Values in Physical Cosmology (Global Journal of Science Frontier Research, 2023)
The research combines literature research and evidence analyses for a cosmological direction in theory building It differentiates the physical causal models from physical cosmology causalities Centromeres are anchored with the partial evidences on the fifth cosmic force between the black hole and the white hole on NGC 3034 The fission-fusion transition mechanisms with centromeres are analyzed analogous to the black hole and white hole asymptotic momentum Ionization flows of the universe with regard to the origins of life is analyzed and concluded in the research
Keywords: black hole; cation; DNA; nuclear analysis; scission point; white hole